2017
DOI: 10.1124/mol.117.109215
|View full text |Cite
|
Sign up to set email alerts
|

Human Missense Mutations in Regulator of G Protein Signaling 2 Affect the Protein Function Through Multiple Mechanisms

Abstract: Regulator of G protein signaling 2 (RGS2) plays a significant role in alleviating vascular contraction and promoting vascular relaxation due to its GTPase accelerating protein activity toward Gq. Mice lacking RGS2 display a hypertensive phenotype, and several RGS2 missense mutations have been found predominantly in hypertensive human subjects. However, the mechanisms whereby these mutations could impact blood pressure is unknown. Here, we selected 16 rare, missense mutations in RGS2 identified in various human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Consequently, RGS2 -/mice are hypertensive and show prolonged responses to these vasoconstrictors (Heximer et al, 2003). In addition, mutations associated with hypertension in humans (Yang et al, 2005) display reduced protein expression (Bodenstein et al, 2007;Phan et al, 2017). We demonstrated that pharmacological enhancement of RGS2 protein levels correlates with increased function.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Consequently, RGS2 -/mice are hypertensive and show prolonged responses to these vasoconstrictors (Heximer et al, 2003). In addition, mutations associated with hypertension in humans (Yang et al, 2005) display reduced protein expression (Bodenstein et al, 2007;Phan et al, 2017). We demonstrated that pharmacological enhancement of RGS2 protein levels correlates with increased function.…”
Section: Introductionmentioning
confidence: 73%
“…were created from the pCMV-RGS2-ProLabel-C3 construct cloned previously (Sjogren et al, 2012) using QuikChange II site-directed mutagenesis (Agilent Technologies, Santa Clara, CA) according to the manufacturer's instructions. RGS2-V5 (in pcDNA3.2-DEST) was created by Gateway® cloning previously in the lab (Phan et al, 2017). K/R mutations were created using QuikChange II site-directed mutagenesis according to the manufacturer's instructions.…”
Section: Dna Constructs -Rgs2-flag Wt M1 M5 M16 and M33 Were A Kinmentioning
confidence: 99%
“…In a study of non-obese diabetic rats with hyperglycaemia, glycated processes in adipose tissue after MG exposure not only impaired microcirculation in epididymal adipose tissue but also led to hypoxia and insulin resistance [ 5 ]. Based on our transcriptome profiling results, downregulation of the RGS2 gene, which is involved in the regulation of angiotensin-activated signaling [ 40 ], indirectly contributed to vascular complications in adipose tissue after MG exposure. Direct glycation processes altered and impaired the structure and function of intracellular and extracellular matrix proteins and led to microvascular changes in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, if a LoF in RGS4 or other RGS protein is found to contribute to disease progression, such a RGS inhibitor may exacerbate the disease and should thus be avoided. A prime example of the power of this analysis is a recent report on RGS2 human variants (Phan et al, 2017) that are linked to hypertension (Yang et al, 2005). The authors found that these RGS2 human variants, located in the N terminus, reduced RGS2-mediated inhibition of Ca 2+ signaling via protein degradation and mislocalization and provided a mechanism for their association with hypertension.…”
Section: Pharmacological Impact Of Human Variants In Rgs Proteinsmentioning
confidence: 99%
“…In a subsequent study, it was found that the Q2L mutation destabilized RGS2 protein (but was reversed by proteasomal inhibition), whereas Q2R (another SNV found in both cases and controls) did not (Bodenstein et al, 2007). A more recent study demonstrated that four human variants, including Q2L, R188H, R44H, and D40Y, showed reduced capacity to inhibit Ca 2+ release by the angiotensin II receptor (Phan et al, 2017). For further review of RGS2 function in physiology, see Bansal et al (2007).…”
Section: Rgs Proteins In Physiology and Human Diseasementioning
confidence: 99%